# Triangle ABC v2

Area of the triangle is 12 cm square. Angle ACB = 30º , AC = (x + 2) cm, BC = x cm. Calculate the value of x.

Result

x =  -8 cm

#### Solution:

Checkout calculation with our calculator of quadratic equations.

Try calculation via our triangle calculator.

Leave us a comment of example and its solution (i.e. if it is still somewhat unclear...):

Be the first to comment!

#### To solve this example are needed these knowledge from mathematics:

Looking for help with calculating roots of a quadratic equation? Do you have a linear equation or system of equations and looking for its solution? Or do you have quadratic equation? See also our right triangle calculator. See also our trigonometric triangle calculator.

## Next similar examples:

1. House roof
The roof of the house has the shape of a regular quadrangular pyramid with a base edge 17 m. How many m2 is needed to cover roof if roof pitch is 57° and we calculate 11% of waste, connections and overlapping of area roof?
2. Triangle
Calculate the area of ​​the triangle ABC if b = c = 17 cm, R = 19 cm (R is the circumradius).
3. Building
The building I focused at an angle 30°. When I moved 5 m building I focused at an angle 45°. What is the height of the building?
4. Steeple
Steeple seen from the road at an angle of 75°. When we zoom out to 25 meters, it is seen at an angle of 20°. What is high?
5. Square root 2
If the square root of 3m2 +22 and -x = 0, and x=7, what is m?
6. Reference angle
Find the reference angle of each angle:
7. Roots
Determine the quadratic equation absolute coefficient q, that the equation has a real double root and the root x calculate: ?
8. Expression with powers
If x-1/x=5, find the value of x4+1/x4
9. Discriminant
Determine the discriminant of the equation: ?
10. Algebra
X+y=5, find xy (find the product of x and y if x+y = 5)
11. Evaluation of expressions
If a2-3a+1=0, find (i)a2+1/a2 (ii) a3+1/a3
12. Equation
Equation ? has one root x1 = 8. Determine the coefficient b and the second root x2.
13. Solve 3
Solve quadratic equation: (6n+1) (4n-1) = 3n2